Chronic Musculoskeletal Pain and Nutrition: Where Are We and Where Are We Heading?. Issue 12 (20th March 2020) - Elma, Ömer; Yilmaz, Sevilay T.; Deliens, Tom; Clarys, Peter; Nijs, Jo; Coppieters, Iris; Polli, Andrea; Malfliet, Anneleen
Abstract : Nutrition is one of the most important lifestyle factors related to chronic diseases such as cancer, diabetes, and cardiovascular diseases. Additionally, poor diet is also considered a predicting, perpetuating, or underlying factor in chronic musculoskeletal pain. This narrative review provides an overview of current knowledge on the relationship between nutrition and chronic musculoskeletal pain (ie, inflammation, obesity, homeostatic balance, and central sensitization as underlying mechanisms). This review also identifies how dietary intake assessments and nutritional behavior interventions for chronic musculoskeletal pain can be used in clinical practice and identifies areas in need of additional research. Based on the available literature, dietary behavior and quality could have an impact on chronic musculoskeletal pain conditions, but the direction of this impact is unclear. There is a need for additional human nutrition studies that focus on specific musculoskeletal pain conditions and underlying pathologies.